NEW ANALYTICAL TECHNIQUE FOR THE DETERMINATION OF MERCURY (II) BY EXTRACTION SPECTROPHOTOMETRIC METHOD WITH ISONITRISO P-ISOPROPYL ACETOPHENONE PHENYL HYDRAZONE IN SEWAGE WASTES AND SPIKED WATER SAMPLES: Pharmaceutical Science-Analytical Chemistry - RAO, BATTULA SREENIVASA; DUBEY, SOM SHANKAR; VENKATA KIRAN, B. (International Journal of Life Science and Pharma Research, 2011)
A new simple and sensitive extractive spectrophotometric method for the determination of mercury (II) with Isonitriso p-isopropyl Acetophenone Phenyl Hydrazone (HIPAPH) has been developed. Mercury was complexed with HIPAPH to form light yellow color Hg-(HIPAPH)2 complex and was extracted in to methyl isobutyl ketone (MIBK). The complex has maximum absorbance at 395nm. The molar absorbitivity and sandell’s sensitivity of the complex was 2.678x10-3 lit.mole-1.cm-1 and 1.765x10-27g/cm2 respectively. The developed method method obeys Beer’s law in the concentration range of 1.0 to 20 ppm. The composition of the complex (metal: ligand) was 1:2. The developed method was applied for the determination of mercury in sewage waste and spiked water samples.